Pendidikan Keluarga Perspektif Qur’an dan Hadist Tarbawiy - Aidatun Nisrina Nulur Firdaus; Fajarullah Alghifari (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Family is the first organization for children and home for everyone. In society, the family is the basis or first school for children from birth untuk they are adult. In this case, the important of edication for children by parents starts fron childhood to adulthood. Family education includes social sciences, religious, science, social, cultural, and others. In general, the family is responsible for children’s education both in axiology and phycology.